2018
DOI: 10.18332/tpc/93787
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and intensity of smoking among healthcare workers and their attitude and behavior towards smoking cessation in the western region of Saudi Arabia: A Cross-sectional study

Abstract: INTRODUCTION This study aimed to estimate the magnitude of tobacco smoking among healthcare workers (HCWs) and to assess the need to establish a smoking cessation program. METHODS This is an institute survey that targeted HCWs from the following specialties: physicians, allied healthcare professionals and administrative workers who are affiliated to a tertiary healthcare institution in the western region of the Kingdom of Saudi Arabia (KSA). An electronic self-administrated questionnaire was distributed among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 12 publications
2
22
1
1
Order By: Relevance
“…However, the smokers were found to have a lower awareness when compared to the nonsmokers, and their scores were significantly lower in all three of the scales. This finding was consistent with study from Saudi Arabia, in which the authors also reported that current smokers lacked smoking-related knowledge when compared to non-smokers [17].…”
Section: Resultssupporting
confidence: 92%
“…However, the smokers were found to have a lower awareness when compared to the nonsmokers, and their scores were significantly lower in all three of the scales. This finding was consistent with study from Saudi Arabia, in which the authors also reported that current smokers lacked smoking-related knowledge when compared to non-smokers [17].…”
Section: Resultssupporting
confidence: 92%
“…Our study confirmed the less than ideal knowledge of tobacco use and cessation among physicians (average score 4.05/10), however, it shows promising positive beliefs and willingness of physicians to implement services (beliefs and intentions averaging above moderate). In our study, 15% of physicians were current smokers, higher than the national average (12.2%) 13 , but slightly less than the prevalence among healthcare professionals found in the western region of KSA in 2015 (18.4%) 34 . Another study assessed attitudes of surgeons practicing in KSA toward preoperative smoking cessation, and found that more than 70% of patients would like to quit smoking after surgery 35 .…”
Section: Discussioncontrasting
confidence: 68%
“…Naši rezultati su lošiji od rezultata istraživanja sprovedenog u Republici Srpskoj na uzorku od 313 zdravstvenih radnika iz sedam domova zdravlja gde je procenat pušača iznosio 22,7% pri čemu je ova loša navika bila prisutnija među medicinskim sestrama (31,2%) nego među lekarima (9,1%) (17). Takođe, i rezultati drugih istraživača ukazuju na značajno manji procenat pušača među zdravstvenim radnicima (18,19,20) u odnosu na rezultate našeg istraživanja.…”
Section: Diskusijaunclassified